Design, Development And Usability Analysis of Pre-Loved Goods Trading Application With Agile Approach - Suwarno Suwarno; Kristianti Kristianti (STMIK Budi Darma, 2022)
Preloved goods are used goods that are still of good quality. When cleaning the house sometimes found a number of Preloved items, where these items are only used once or not used at all and stored for quite a long time at home. Used goods that accumulate in the house make the room in the house even narrower. Therefore, Preloved items are more profitable if they are sold rather that being thrown away or stored. Besides that, selling Preloved items can get extra money and help in environmental preservation. So the writer got an idea how to use a website as a marketplace to sell Preloved goods in Batam city, namely the Batam Preloved Shop. Batam residents get information on Preloved items they want to buy through this marketplace. The method used in designing and developing the Batam Preloved Shop is Agile. Next, test the system by testing the Black Box and System Usability Scale (SUS). The results of the Black Box test show that the Batam Preloved Shop system is running as expected and an analysis of user satisfaction using the System Usability Scale (SUS) obtains an average value of 81, so it can be concluded that the Batam Preloved Shop system has been running well according to its functions and uses